Capacities and needs assessment of gender research in CGIAR - Zaremba, Haley; Elias, Marlène; Rietveld, Anne; Marimo, Pricilla; Kropff, Wietske (2022)
"In November 2020, CGIAR commissioned Michigan State University’s Center for Gender in Global Context (GenCen) to conduct a capacities and needs assessment (CNA) to determine, with the participation of stakeholders throughout CGIAR and (to a lesser extent) the broader agricultural research for development (AR4D) network, how the GENDER Platform could best strengthen the capacities needed to achieve the Platform’s desired outcomes. Four overarching questions guided the CNA: • What is quality gender research? • What is the current capacity of CGIAR to undertake such research? • Does the CGIAR environment enable quality gender research? • How can the GENDER Platform support this research?"